Research advances of Zanthoxylum bungeanum Maxim. polyphenols in inflammatory diseases - Qi, Jinxin; Pan, Zhaoping; Wang, Xiaoyun; Zhang, Nan; He, Gu; Jiang, Xian (Frontiers in Immunology, 2024)
Zanthoxylum bungeanum Maxim., commonly known as Chinese prickly ash, is a well-known spice and traditional Chinese medicine ingredient with a rich history of use in treating inflammatory conditions. This review provides a comprehensive overview of the botanical classification, traditional applications, and anti-inflammatory effects of Z. bungeanum, with a specific focus on its polyphenolic components. These polyphenols have exhibited considerable promise, as evidenced by preclinical studies in animal models, suggesting their therapeutic potential in human inflammatory diseases such as ulcerative colitis, arthritis, asthma, chronic obstructive pulmonary disease, cardiovascular disease, and neurodegenerative conditions. This positions them as a promising class of natural compounds with the potential to enhance human well-being. However, further research is necessary to fully elucidate their mechanisms of action and develop safe and effective therapeutic applications.